2022
DOI: 10.28985/1322.jsc.02
|View full text |Cite
|
Sign up to set email alerts
|

Twitter discourse around competitive cycling and sports-related concussion

Abstract: The purpose of this study was to explore the cycling community’s online interactions with sports-related concussion within competitive cycling. Through an analysis of twitter data (n=196), this study examined the limited discourse related to the problem of concussion in cycling. The results found overall engagement and awareness of concussion in cycling was low but has been increasing year on year from 2008 to 2019. Thematic analysis of the data found three main themes within the online cycling community on Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…They had difficulties comprehending how dopers can reconcile their behaviour with their conscience. Some participants suggested that dopers do not experience a value conflict, while others proposed that dopers justify their actions through a process of normalisation [e.g., (56)(57)(58)] or moral disengagement (59). They also indicated that the acceptance of doping use happens gradually, starting with small steps and eventually becoming an integral part of training practice.…”
Section: Athletes Condemn Doping But Understand the Circumstancesmentioning
confidence: 99%
“…They had difficulties comprehending how dopers can reconcile their behaviour with their conscience. Some participants suggested that dopers do not experience a value conflict, while others proposed that dopers justify their actions through a process of normalisation [e.g., (56)(57)(58)] or moral disengagement (59). They also indicated that the acceptance of doping use happens gradually, starting with small steps and eventually becoming an integral part of training practice.…”
Section: Athletes Condemn Doping But Understand the Circumstancesmentioning
confidence: 99%